3D printed oxidized alginate-gelatin bioink provides guidance for C2C12 muscle precursor cell orientation and differentiation via shear stress during bioprinting - Distler, Thomas; Solisito, Aditya; Schneidereit, Dominik; Friedrich, Oliver; Detsch, Rainer; Boccaccini, Aldo R. (Biofabrication, 2020)
Biofabrication can be a tool to three-dimensionally (3D) print muscle cells embedded inside hydrogel biomaterials, ultimately aiming to mimic the complexity of the native muscle tissue and to createin-vitromuscle analogues for advanced repair therapies and drug testing. However, to 3D print muscle analogues of high cell alignment and synchronous contraction, the effect of biofabrication process parameters on myoblast growth has to be understood. A suitable biomaterial matrix is required to provide 3D printability as well as matrix degradation to create space for cell proliferation, matrix remodelling capacity, and cell differentiation. We demonstrate that by the proper selection of nozzle size and extrusion pressure, the shear stress during extrusion-bioprinting of mouse myoblast cells (C2C12) can achieve cell orientation when using oxidized alginate-gelatin (ADA-GEL) hydrogel bionk. The cells grow in the direction of printing, migrate to the hydrogel surface over time, and differentiate into ordered myotube segments in areas of high cell density. Together, our results show that ADA-GEL hydrogel can be a simple and cost-efficient biodegradable bioink that allows the successful 3D bioprinting and cultivation of C2C12 cellsin-vitroto study muscle engineering.
Keywords: myoblasts; muscle tissue engineering; 3D printing; oxidized alginate; gelatin; hydrogel